Effects of Immediate Coating on Unset Composite with Different Bonding Agents to Surface Hardness - Krajangta, Nantawan; Ninbanjong, Supissara; Khosook, Sunisa; Chaitontuak, Kanjana; Klaisiri, Awiruth (European Journal of Dentistry, 2022)
Objectives This study evaluated the surface microhardness of composite, affected by surface coating with different dental adhesive systems.Materials and Methods A total of 100 composite discs were divided into five groups. Group 1 was uncoated (control group C), and groups 2 to 5 were coated with different adhesive systems (OptiBond FL: FL, OptiBond SOLO Plus: SOLO, OptiBond XTR: XTR, and OptiBond All in one: AIO, respectively). The Vickers microhardness (VHN) was measured without and with 500 thermocycles.Statistical Analysis The data were analyzed using two-way ANOVA and Tukey's posthoc test at the 95% confidence level.Results At 24 hours, the VHN of C (59.96 ± 3.68) and FL (59.83 ± 4.54) were significantly higher than SOLO (51.73 ± 4.63) and AIO (51.45 ± 4.11). The VHN of XTR (54.96 ± 3.68) was not significant compared with that of C and all other groups. After thermocycling, VHN were significantly decreased in all groups. However, there were no significant differences among all groups.Conclusions At 24 hours, composite coated with different adhesive systems have different effects to VHN. Thermocycling all adhesive resin systems coated on composite surface significantly decreased the VHN.
Keywords: dental adhesive systems; microhardness; surface coating; thermocycling